2021
DOI: 10.2196/25925
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Anorexia Nervosa on Social Media: Textual, Visual, Relational, Behavioral, and Demographical Analysis

Abstract: Background Eating disorders are psychological conditions characterized by unhealthy eating habits. Anorexia nervosa (AN) is defined as the belief of being overweight despite being dangerously underweight. The psychological signs involve emotional and behavioral issues. There is evidence that signs and symptoms can manifest on social media, wherein both harmful and beneficial content is shared daily. Objective This study aims to characterize Spanish-spea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…This can provide a characterization of the symptoms of psychological disorders such as AN. In this regard, the study by Ramírez-Cifuentes et al [5] characterized different stages of AN on Spanish-speaking Twitter users by combining the analysis of text, images, and social interactions.…”
Section: Characterization and Assessment Of Mental Disorders On Socia...mentioning
confidence: 99%
See 1 more Smart Citation
“…This can provide a characterization of the symptoms of psychological disorders such as AN. In this regard, the study by Ramírez-Cifuentes et al [5] characterized different stages of AN on Spanish-speaking Twitter users by combining the analysis of text, images, and social interactions.…”
Section: Characterization and Assessment Of Mental Disorders On Socia...mentioning
confidence: 99%
“…On a daily basis, many people are increasingly using social media platforms to share their feelings and moods. This creates a unique opportunity to proactively identify linguistic patterns that correlate with mental disorders [5,6]. Early risk prediction of depression and anorexia [7] and suicide risk assessment [8,9] are just some examples of different initiatives that have fostered research on the interaction between language and mental health disorders on web-based social media and the application of ML to address such challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers differentiate between communities that post about anorexia—for example, pro-ana, anti-ana, and pro-recovery communities (Chancellor et al, 2016). 2 They note specificities in the language used by pro-ana and pro-recovery people, such as the use of personal pronouns, the emotional tone of posts, and the topics raised (Chancellor et al, 2016; Ramírez-Cifuentes et al, 2021). However, contemporary scholarship on these communities has shown that the borders between them blur over time and might be considered artificial; therefore, it is questionable whether such distinctions are reasonable (Cobb, 2017; Wang et al, 2019).…”
Section: Self-representations Of Anorexia On Social Mediamentioning
confidence: 99%
“…The relations with the personality traits were found not only for the OSM photo avatars [1,9] but for people's avatars in other virtual activities [10,11]. In the area of psychological research, it was shown that avatars of individuals who are prone to depression often depict a single person and are biased toward the gray spectrum [12]. Similar relationships between the graphic content of a user's online social network profile and his, her or their psychological peculiarities can be traced for other conditions as well [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, such quantified relationships between an avatar's graphical characteristics and personality traits can be used in automated decision support systems [15] in various fields, such as marketing and psychological and career counseling. For example, there exist automated systems for determining depression [12,16]. Moreover, these associations can be viewed as a part of the user profiling process that plays an important role in assessing an estimation of the users' protection from social engineering attacks [17][18][19].…”
Section: Introductionmentioning
confidence: 99%